Reading and writing: Psychoanalytical treatment in a case of paranoia - Gonçalves Freire, Joyce Marly; Campos De Cerqueira Leite, Adriana; Bueno, Débora Siqueira; Portella, Luciana Balbo; Ribes, Sílvia Igleses; Assadi, Tatiana Carvalho; Colucci, Vera Lúcia; Costa Pereira, Mário Eduardo (Springer Nature, 2005)
Difficulties encountered in clinical work with psychoses require psychoanalytical approaches different from those used for treating neurosis. The authors use a clinical case of a paranoiac patient to highlight the role played by writing, drawing, and painting in the psychoanalytical treatment of psychosis. They also discuss the role of the reader-analyst in this patient's transferential process, which led to the emergence of a new subjectivity. © 2005 Association for the Advancement of Psychoanalysis.
Keywords: paranoia; psychoanalysis; psychosis; reading; writing